Relationships between Community Reintegration and Clinical and Psychosocial Attributes in Individuals with Spinal Cord Injury in a Nigerian City (2018)
Background: The bio-psychosocial model for comprehensive understanding of community reintegration among individuals with spinal cord injury (SCI) varies across communities. Yet, information about community reintegration in Nigeria is not available. Objective: To investigate the association between community reintegration and clinical and psychosocial attributes among Nigerians with SCI. Methods: Fifty individuals (31 females; 19 males) with SCI aged 38.6 ± 11.1 years participated in this longitudinal survey. Pain, functional ability, and severity of injury were assessed at discharge and at 1, 2, and 3 months post discharge from inpatient care using the Visual Analogue Scale (VAS), FIM®, and American Spinal Injury Association Impairment Scale (AIS), respectively. Self-esteem (SE), social support (SS), and depression were also assessed using the Self-Esteem Questionnaire, Social Support Questionnaire, and Beck Depression Inventory, respectively. CR was assessed at 1, 2, and 3 months post-discharge using the Reintegration to Normal Living Index (RNLI). Data were analyzed using Spearman’s rho correlation and Friedman test. Results: The psychosocial and clinical attributes were significantly different from baseline and across the 3 months post-discharge (p < .0001), except for SS. CR significantly correlated with level of injury, function ability, SE, and depression across the 3 months post-discharge (p < .01). CR was significantly correlated with SS only at 1 month post-discharge (p = .027). Conclusion: Individuals with SCI had significant improvement in clinical and psychosocial attributes from discharge to 3 months post-discharge. Improvements in these variables were associated with better reintegration into the community.